1999
DOI: 10.1016/s0002-9440(10)65287-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neurotrophins and their Receptors in Human Bone Marrow

Abstract: The expression of neurotrophins and their receptors, the low-affinity nerve growth factor receptor (p75 LNGFR ) and the Trk receptors (TrkA , TrkB, and TrkC) , was investigated in human bone marrow from 16 weeks fetal age to adulthood. Using reverse transcription-polymerase chain reaction , all transcripts encoding for catalytic and truncated human TrkB or TrkC receptors were detected together with trkAI transcripts , whereas trkAII transcripts were found only in control nerve tissues. Transcripts for the homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
106
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 60 publications
(93 reference statements)
6
106
0
2
Order By: Relevance
“…Remarkably, we found that all these specimens (ACC1-6) expressed the canonical isoform b that encodes a fully active protein (NM_002530), but also contained splicoform d (NM_001243101) that lacks exon 10 producing an 8-amino-acid (aa) in-frame deletion in the juxtamembrane TrkC domain. This isoform, which was expressed in ACC at levels similar to isoform b (data not shown), was previously described as a polymorphism, 41 but its biological significance remains unclear. TrkC signaling varies depending on the availability of its ligand, NT-3.…”
Section: Introductionmentioning
confidence: 84%
“…Remarkably, we found that all these specimens (ACC1-6) expressed the canonical isoform b that encodes a fully active protein (NM_002530), but also contained splicoform d (NM_001243101) that lacks exon 10 producing an 8-amino-acid (aa) in-frame deletion in the juxtamembrane TrkC domain. This isoform, which was expressed in ACC at levels similar to isoform b (data not shown), was previously described as a polymorphism, 41 but its biological significance remains unclear. TrkC signaling varies depending on the availability of its ligand, NT-3.…”
Section: Introductionmentioning
confidence: 84%
“…Although the mechanisms whereby BMMCs promote angiogenesis in vivo remain unclear, our current coculture experiments indicate that BMMCs-induced proliferation of ECs is at least partially attributable to soluble factors. It has been reported that BMCs such as BMMCs [22,46,47] and MSCs [48][49][50] secrete multiple growth factors, including VEGF, glia-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and hepatocyte growth factor (HGF). In addition, they have been considered to be part of mechanisms responsible for angiogenic, antiapoptotic, and mitogenic effects after cell transplantation [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…However, stromal cells in the bone marrow microenvironment secrete NGF and other cytokines (41); thus, the enhanced expression of the TRKA receptor on AML1-ETO-positive cells could impart a selective growth advantage. The recent finding that AML1-ETO deregulates genes involved in DNA repair underscores the importance of promoting preleukemic stem cell growth to allow for the acquisition of cooperating mutations that could lead to a fully transformed state (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although NGF͞ TRKA signaling has been most intensively studied in the nervous system, it also participates in hematopoiesis, prostate cancer cell behavior, and angiogenesis (38)(39)(40). NGF is normally expressed by bone marrow stromal cells (41), whereas TRKA is expressed in hematopoietic progenitor cells (42).…”
mentioning
confidence: 99%